2010
DOI: 10.1108/00035591011058192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu content on the corrosion of Al‐Si eutectic alloys in acidic solutions

Abstract: Purpose -The purpose of this paper is to understand corrosion behavior of different Cu-containing Al-Si-x% Cu alloys (x: 1 wt% Cu, 2 wt% Cu, 3 wt% Cu, 4 wt% Cu, and 5 wt% Cu) in 0.1 M HCl and 0.1 M H 2 SO 4 . Design/methodology/approach -Potentiodynamic, chronoamperometric and impedance measurements were applied to specimens to obtain their electrochemical characteristics. For the long-term analyses, hydrogen evolution with immersion time (V-t) was measured. The corroded surfaces of the alloys were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…1 Among these materials, aluminium alloys have been considered and studied by many researchers. [2][3][4][5][6] Owing to the weak mechanical properties of pure aluminium, many works have been performed to enhance the properties of aluminium by alloying and heat treatment. 7 Through alloying, high mechanical strength can be obtained by the formation of a fine and homogeneous distribution of intermetallic compounds, which must be stable at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among these materials, aluminium alloys have been considered and studied by many researchers. [2][3][4][5][6] Owing to the weak mechanical properties of pure aluminium, many works have been performed to enhance the properties of aluminium by alloying and heat treatment. 7 Through alloying, high mechanical strength can be obtained by the formation of a fine and homogeneous distribution of intermetallic compounds, which must be stable at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the wide application of aluminum alloys, considerable attention has been devoted to the corrosion behavior of the alloys in various corrosive environments. Zor et al [2] reported that the increase of Cu content increased the volume fraction of θ-phase particles and decreased the corrosion rate of Al-Si eutectic alloy in acidic solution. Barros et al [3] reported that the addition of Mg to the Al-Cu alloy resulted in a lower polarization resistance and higher corrosion current density of the alloy, which accelerated the corrosion of the alloy in 0.5 M NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…Ligas de alumínio podem ser produzidas através da adição de adequados elementos de liga, tais como Cu, Mg, Zn e por adequados procedimentos de tratamento de calor (Zor et al, 2010;Andreatta et al, 2003;Cabot et al, 1995).…”
Section: Introductionunclassified